THE EFFECT OF COMPETENCY ON LECTURERS' PERFORMANCE WITH ORGANIZATIONAL CULTURE AS AN INTERVENING VARIABLE IN HIGHER EDUCATION IN PEMATANGSIANTAR - Syaifuddin, Syaifuddin; Sihombing, Sabar Dumayanti; Lubis, Fajar Rezeki Ananda; Simanjuntak, Dahnil Anzar (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2026)
The decline in lecturer quality is undoubtedly caused by various factors, both internal and external. This study will examine the influence of competency on lecturer performance, with organizational culture as an intervening variable at universities in Pematangsiantar. The sample size for this study was 220 people. The results indicate that competency (X1) directly and positively influences organizational culture (Z) and lecturer performance (Y) at universities in Pematangsiantar. Furthermore, organizational culture (Z) can indirectly mediate the relationship between competency (X1) and lecturer performance (Y) at universities in North Sumatra.